Pemanfaatan Teknologi dalam Mewujudkan Sustainable And Productive Life Masyarakat Kelurahan Pradah Kalikendal, Kecamatan Dukuh Pakis, Surabaya - Prihartini Widiyanti; Franky Chandra Satria Arisgraha; Fitriyatul Qulub (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
One of the problems that exist in the community of Pradah Kalikendal Village, which is the largest sub-district in Dukuh Pakis District, Surabaya, is the waste of water that occurs during ablution and increasing chronic fatigue in the community which has an impact on reducing community productivity. Based on this, Airlangga University launched a community service program with the theme